Hubungan Kemandirian, Sikap, dan Motivasi dengan Hasil Belajar Biologi Kelas XI IPA SMA - Nurhidayah Hasan; Firdaus Daud; Rachmawaty Rachmawaty (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Students' Biology learning outcomes are influenced by two factors, namely internal and external factors. Internal factors that can influence learning outcomes are independence, attitude and learning motivation. This research aims to investigate the relationship between independence, attitudes and learning motivation and biology learning outcomes. This research is ex post facto research. The research instrument is a questionnaire used to obtain data on independence, attitudes and motivation to learn. Documentation is used to obtain biology learning outcomes scores. Data collection on independence, attitudes and motivation to learn was carried out through giving questionnaires to students. Learning outcome data is obtained from daily test scores. Data were analyzed using descriptive and inferential statistical analysis with product moment correlation tests, simple and multiple regression. The results of the research show that (i) students' learning independence is in the high category, (ii) students' learning attitudes are in the positive category, (iii) students' learning motivation is in the high category, (iv) students' biology learning outcomes are in the very high category, (v) there is a strong relationship between independence and biology learning outcomes, with a correlation value of 0.680, (vi) there is a strong relationship between attitudes and biology learning outcomes, with a correlation value of 0.663, (vii) there is a strong relationship moderate between motivation and biology learning outcomes, with a correlation value of 0.453, (viii) there is a strong relationship between independence, attitude and motivation and biology learning outcomes with a correlation value of 0.730.